Confronting the public health challenge of inaccessible COVID-19 home tests: insights from the RADx® Tech Accessibility Initiative - Kennedy, Emily B.; Noble, Kimberly; Leite, Kevin; Downing, Maren; Dolphin, Samuel; Cirrincione, Mia; Walsh, Brian (Frontiers in Public Health, 2025)
COVID-19 home tests first distributed by the U.S. Government in early 2022 proved inaccessible to Americans with no vision, low vision, limited dexterity, and certain aging-related impairments. The National Institute of Biomedical Imaging and Bioengineering (NIBIB) leveraged a multimillion-dollar investment to address this challenge via the Rapid Acceleration of Diagnostics (RADx®) Tech Accessibility Initiative. What follows is a case study report on the March 2022–June 2023 implementation of this initiative, which was later expanded into a larger-scale program called RADx Tech III (September 2022–present). The initiative unveiled a substantial gap in resources guiding accessible product development and applied crisis response funding to bridge this gap. Beyond the primary goal of improving accessibility of COVID-19 home tests, the initiative was successful in developing an expert resource pool, documenting best practices for design of accessible home tests, and generating/validating a framework for future accessibility initiatives.